2007
DOI: 10.1093/jnci/djm025
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Bisphosphonate Therapy and Inflammatory Conditions or Surgery of the Jaw: A Population-Based Analysis

Abstract: Users of intravenous bisphosphonates had an increased risk of inflammatory conditions, osteomyelitis, and surgical procedures of the jaw and facial bones. The increased risk may reflect an increased risk for osteonecrosis of the jaw.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
97
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 20 publications
1
97
0
5
Order By: Relevance
“…Since 2003, when Marx (4) published a series of thirtysix cases of osteonecrosis associated with bisphosphonates, numerous studies have been carried out which relate the occurrence of osteonecrosis in maxillary structures, mainly the mandible, associated with intravenous bisphosphonates following oral surgery, mainly exodontias (1,(4)(5)(6)(7)(8)(9). However, the topic of the present review is the incidence of osteonecrosis related to dental implant placement in patients undergoing treatment with oral bisphosphonates; our findings are shown in table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Since 2003, when Marx (4) published a series of thirtysix cases of osteonecrosis associated with bisphosphonates, numerous studies have been carried out which relate the occurrence of osteonecrosis in maxillary structures, mainly the mandible, associated with intravenous bisphosphonates following oral surgery, mainly exodontias (1,(4)(5)(6)(7)(8)(9). However, the topic of the present review is the incidence of osteonecrosis related to dental implant placement in patients undergoing treatment with oral bisphosphonates; our findings are shown in table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The survey has identified 16,073 cancer patients treated with iv bisphosphonates between 1995 and 2003 who were matched with 28,698 bisphosphonate nonusers. The conclusion of this study is that users of iv bisphosphonates had an increased risk of inflammatory conditions, osteomyelitis, and surgical procedures of the jaws and facial bones which may reflect an increased risk for BRONJ [34]. It is of historical interest to mention that osteonecrosis of the jaws was observed in the 19th and early 20th centuries in patients exposed to white phosphorus.…”
mentioning
confidence: 85%
“…A recent survey of 1,086 oncology patients reported that 3.8% of multiple myeloma patients, 2.5% of breast cancer patients and 2.9% of prostate cancer developed BRONJ [33]. Of great relevance is a recent population-based study in which the data from the USA SEER program linked to Medicare claims were used [34]. The survey has identified 16,073 cancer patients treated with iv bisphosphonates between 1995 and 2003 who were matched with 28,698 bisphosphonate nonusers.…”
mentioning
confidence: 99%
“…Osteonecrosis of the jaw, described as a painful refractory bone exposure in the jaws is a serious complication of bisphosphonate usage [47]. It is seldom seen in relation to the usage of oral bisphosphonates.…”
Section: Therapeutic Actionsmentioning
confidence: 99%